Ultrastructural muscle and neuro-muscular junction alterations in polymyositis - L. L. Babakova; O. M. Pozdnyakov (Нервно-мышечные болезни, 2015)
Ultrastructural analysis of 7 biopsies from m.palmaris longus and m.deltoideus in patients with confirmed polymyositis revealed alterationand degeneration of muscle fibers and anomalies of neuro-muscular junction (NMJ). The NMJ abnormalities and following denervation ofmuscle fibers in polymyositis start with subsynaptic damages. The occurance of regeneration features in muscle fibers at any stage is characteristic for PM.